Toxicological Evaluation of Vanillin Flavor in E-Liquid Aerosols on Endothelial Cell Function: Findings from the Replica Project - R. Emma; A. Sun; K. Partsinevelos; S. Rust; V. Volarevic; R. Lesmana; A. Giordano; H. Goenawan; M. I. Barliana; A. Arsenijevic; N. Kastratovic; V. Markovic; et al. (Cardiovascular Toxicology, 2026)
There are challenges that require collaboration among researchers to ensure that tobacco harm reduction strategies are evidence-based. A key challenge is evaluating the safety of flavors in e-cigarettes. Many flavorings are deemed “generally recognized as safe” (GRAS) for ingestion, but this does not guarantee their safety when inhaled. The Replica international research group is dedicated to the replication of studies on tobacco alternatives. As part of this effort, the group conducted a conceptual replication of the vanillin-specific experiments from the study by Fetterman et al. (2018), with the goal of validating their conclusions regarding this compound. We used Aspire Zelos 3 e-cigarette and prepared e-liquids containing propylene glycol, vegetable glycerin, and vanillin. The e-liquids were vaporized under regular (1 Ohm coil, 14 watts) and sub-Ohm (0.3 Ohm coil, 200 °C) settings using a vaping machine, following ISO20768:2018 puffing regime. The vapor was collected into a trapping solution to prepare aqueous extracts for treating human aortic endothelial cells. We evaluated cytotoxicity, oxidative stress, nitric oxide bioavailability, and inflammation addressing some gaps reported in the original study. We observed some harmful effects mostly attributable to ethanol used to trap vanillin, but no harmful effects from vanillin. Our results confirm the endothelial cell dysfunction observed in the original paper, but clarify that these effects are mainly attributable to ethanol and not to vaporized vanillin, indicating that, under the experimental conditions applied, vanillin does not elicit significant adverse effects on vascular endothelial cells. However, further research is needed to confirm its toxicological profile. Graphical Abstract Created in BioRender. https://BioRender.com/rn8dt1m .

Tendon-Targeted Knockout of Collagen XII Disrupts Murine Achilles Tendon Structure, Function, and Gene Expression at Later Stages of Postnatal Development - Michael S. DiStefano; Rebecca L. Betts; Courtney A. Nuss; Srish S. Chenna; Louis J. Soslowsky (Annals of Biomedical Engineering, 2026)
Tendons rely on hierarchical extracellular matrix organization for proper growth and mechanical function, but the tendon-specific role of collagen XII in this process remains poorly defined. The purpose of this study was to determine how tendon-targeted loss of collagen XII influences Achilles tendon structure, mechanics, and gene expression across key stages of postnatal development. Using tendon-targeted Scx-Cre; Col12a1 flox/flox knockout mice, we evaluated Achilles tendons at postnatal days 10, 30, and 60 with histological, ultrastructural, biomechanical, and compositional approaches. Mechanical testing revealed progressive deficits in knockout tendons, including reduced maximum load, stiffness, and modulus at P30 and P60, as well as altered viscoelastic properties across all timepoints. Structural analyses demonstrated increased tendon length across all timepoints and greater cell density, rounder nuclei, impaired collagen fiber realignment, and smaller fibril diameters with disrupted maturation, with more notable changes at later postnatal developmental timepoints. Gene expression profiling revealed early downregulation of matrix and signaling genes at P10, followed by upregulation of matrix remodeling and matricellular genes at P30 and P60, consistent with a persistent, maladaptive remodeling response. Together, these findings establish collagen XII as a critical regulator of hierarchical tendon development, integrating fibrillogenesis, cell morphology, mechanical function, and gene expression to ensure proper tendon development.

gSeaGen code by KM3NeT: An efficient tool to propagate muons simulated with CORSIKA - S. Aiello; A. Albert; A.R. Alhebsi; M. Alshamsi; S. Alves Garre; A. Ambrosone; F. Ameli; M. Andre; L. Aphecetche; M. Ardid; S. Ardid; H. Atmani; et al. (Computer Physics Communications, 2025)

Upstream Proteolysis by Ste24 does not Require a C-Terminal Methyl Ester as Revealed Using 33-Residue a-Factor Precursor Peptide Substrates Synthesized via Epimerization-Free Methods - Taysir K. Bader; Shanica M. Brown; Christine A. Hrycyna; Mark D. Distefano (International Journal of Peptide Research and Therapeutics, 2025)

Chronic effects of metal releases from historical mining on threatened crayfish in Madison County Missouri, USA - A. L. Allert; D. Cleveland; R. J. DiStefano; M. L. Wildhaber; L. K. Lueckenhoff (Ecotoxicology, 2024)

Sex differences in the association between skeletal muscle energetics and perceived physical fatigability: the Study of Muscle, Mobility and Aging (SOMMA) - Emma L. Gay; Paul M. Coen; Stephanie Harrison; Reagan E. Garcia; Yujia Qiao; Bret H. Goodpaster; Daniel E. Forman; Frederico G. S. Toledo; Giovanna Distefano; Philip A. Kramer; Sofhia V. Ramos; Anthony J. A. Molina; et al. (GeroScience, 2024)

P01-33 Toxicity induced by cigarette smoke and electronic cigarette aerosols - K. Partsinevelos; R. Emma; A. Distefano; G. Carota; S. Rust; R. Pulvirenti; D. Campagna; R. Polosa; M. Caruso; G. Li Volti (Toxicology Letters, 2024)

Embedded software of the KM3NeT central logic board - S. Aiello; A. Albert; S. Alves Garre; Z. Aly; A. Ambrosone; F. Ameli; M. Andre; E. Androutsou; M. Anghinolfi; M. Anguita; L. Aphecetche; M. Ardid; et al. (Computer Physics Communications, 2024)

Towards a cohesive strategy for the conservation of the United States’ diverse and highly endemic crayfish fauna - Christopher A. Taylor; Robert J. DiStefano; Eric R. Larson; James Stoeckel (Hydrobiologia, 2019)

Genetic structure analysis and selection of a core collection for carob tree germplasm conservation and management - M. Di Guardo; F. Scollo; A. Ninot; M. Rovira; J. F. Hermoso; G. Distefano; S. La Malfa; I. Batlle (Tree Genetics & Genomes, 2019)

Receptor-mediated toxicity of human amylin fragment aggregated by short- and long-term incubations with copper ions - Giuseppe Caruso; Donatella A. Distefano; Paolo Parlascino; Claudia G. Fresta; Giuseppe Lazzarino; Susan M. Lunte; Vincenzo G. Nicoletti (Molecular and Cellular Biochemistry, 2017)

Effects of historical lead–zinc mining on riffle-dwelling benthic fish and crayfish in the Big River of southeastern Missouri, USA - A. L. Allert; R. J. DiStefano; J. F. Fairchild; C. J. Schmitt; M. J. McKee; J. A. Girondo; W. G. Brumbaugh; T. W. May (Ecotoxicology, 2013)

Proteolytic cleavage of plant proteins by peroxisomal endoproteases from senescent pea leaves - Jos M. Palma; Luis A. del Ro; Stefania Distefano; Iva McCarthy (Planta, 1999)

System analysis and estimation of key parameters of thyroid hormone metabolism in sheep - Kitchener C. Wilson; Joseph J. DiStefano; Delbert A. Fisher; Joseph Sack (Annals of Biomedical Engineering, 1977)